Maternal Deaths from COVID-19 in Brazil: Increase during the Second Wave of the Pandemic - Carlos André Scheler; Michelle Garcia Discacciati; Diama Bhadra Vale; Giuliane Jesus Lajos; Fernanda Garanhani Surita; Julio Cesar Teixeira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To compare death rates by COVID-19 between pregnant or postpartum and nonpregnant women during the first and second waves of the Brazilian pandemic. Methods In the present population-based evaluation data from the Sistema de Informação da Vigilância Epidemiológica da Gripe (SIVEP-Gripe, in the Portuguese acronym), we included women with c (ARDS) by COVID-19: 47,768 in 2020 (4,853 obstetric versus 42,915 nonobstetric) and 66,689 in 2021 (5,208 obstetric versus 61,481 nonobstetric) and estimated the frequency of in-hospital death. Results We identified 377 maternal deaths in 2020 (first wave) and 804 in 2021 (second wave). The death rate increased 2.0-fold for the obstetric (7.7 to 15.4%) and 1.6-fold for the nonobstetric groups (13.9 to 22.9%) from 2020 to 2021 (odds ratio [OR]: 0.52; 95% confidence interval [CI]: 0.47-0.58 in 2020 and OR: 0.61; 95%CI: 0.56- 0.66 in 2021; p < 0.05). In women with comorbidities, the death rate increased 1.7-fold (13.3 to 23.3%) and 1.4-fold (22.8 to 31.4%) in the obstetric and nonobstetric groups, respectively (OR: 0.52; 95%CI: 0.44-0.61 in 2020 to OR: 0.66; 95%CI: 0.59-0.73 in 2021; p <0.05). In women without comorbidities, the mortality rate was higher for nonobstetric (2.4 times; 6.6 to 15.7%) than for obstetric women (1.8 times; 5.5 to 10.1%; OR: 0.81; 95%CI: 0.69-0.95 in 2020 and OR: 0.60; 95%CI: 0.58-0.68 in 2021; p <0.05). Conclusion There was an increase in maternal deaths from COVID-19 in 2021 compared with 2020, especially in patients with comorbidities. Death rates were even higher in nonpregnant women, with or without comorbidities.